THE INFLUENCE OF WORK ENVIRONMENT, WORK ABILITY, EMPOWERMENT AND TRAINING ONEMPLOYEE PERFORMANCE AT PT. SYAUKAT SEJAHTERA IN GANDAPURA, BIREUEN REGENCY - Moliana; Hamdiah; Em. Yusuf Iis; Likdanawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research aims to determine the influence of the work environment, work ability, empowerment and training on employee performance at PT. Prosperous Syaukat in Gandapura, Bireuen Regency. The independent variables in this research are Work Environment (X1), Work Ability (X2), Empowerment (X3) and Training (X4). Meanwhile, the dependent variable is Employee Performance (Y). This type of research uses quantitative methods and data collection uses a questionnaire containing questions and statements by distributing them to the employees concerned at PT. Prosperous Syaukat in Gandapura, Bireuen Regency. By giving scores using a Likert scale. This research was conducted with a population of 142 employees, where sampling used the saturated sample method. This research uses multiple linear regression analysis with the SPSS (Statistical Program For Social Science) program. The results of this research indicate that the work environment has a positive and significant effect on employee performance at PT. Syaukat Sejahtera in Gandapura, Bireuen Regency, Ability has a positive effect on employee performance at PT. Syaukat Sejahtera in Gandapura, Bireuen Regency, Empowerment has a positive and significant effect on employee performance at PT. Syaukat Sejahtera in Gandapura, Bireuen Regency, while training has a negative effect on employee performance at PT. Prosperous Syaukat in Gandapura, Bireuen Regency. The better the work environment, work abilities, empowerment and training in an organization, the better the performance produced by employees.